Hashimoto's encephalopathy presenting with acute confusional state in a patient with hypothyroidism - Naglaa Fathy Barseem; Mohamed Ahmed Helwa (SpringerOpen, 2015)
Hashimoto's encephalopathy is a neurological disorder of unknown etiology associated with thyroid autoimmunity. The disease may present as two types, a sudden vasculitic type or a progressive subacute type associated with cognitive dysfunction, confusion and memory loss. We report a case of a 6 year old previously healthy Egyptian female , who developed a subacute onset of declining upper brain function. Serologic studies demonstrated high levels of antithyroid antibodies. Electroencephalographic and magnetic resonance image findings were consistent with Hashimoto's encephalopathy. Hashimoto's encephalopathy is a diagnosis of exclusion. This unusual disorder is often underrecognized because of multiple neurocognitive manifestations; therefore, it is important to be aware of the clinical manifestations to make a correct diagnosis.